Microstructural Dependency of Diffusion in Glass Flake-Reinforced Vinyl Ester Resins - Bryan B Parajito; Masatoshi Kubouchi; Hiroyuki Tomita; Saiko Aoki (ASEAN Journal of Chemical Engineering, 2012)
Vinyl ester resins are utilized for long-term corrosion protection of metal, alloy, and concrete substrates against concentrated acids, alkalis, and solvents at high temperature. Glass flakes are usually added as fillers to reduce chemical diffusion within the vinyl ester matrix. A common industry practice is to use glass flakes with large aspect ratio, high volume fraction, and in parallel alignment to surface in chemical contact for barrier applications. During processing and curing of glass flake-filled vinyl ester resins, irregular microstructures such as reduced flake aspect ratio and random orientation of flakes are commonly observed. Such microstructures can affect the overall chemical diffusion, resulting to barrier properties less predictable by simple diffusion models. Therefore, in this study, a simple 2D random walk simulation procedure is used in attempt to estimate the microstructural dependency of diffusion in glass flake-reinforced vinyl ester resins. While the random walk simulations are in good agreement with the tortuosity-based diffusion models in terms of microstructural effects, in most cases the simulation results are inconsistent with the experimental measurements of acid diffusion in glass flake-filled vinyl ester resins. A possible cause for this is the poor adherence of vinyl ester resin to glass flakes. Osmotic cracks are also formed during immersion which also influences overall diffusion through the material.